Comparative effects of microvascular and macrovascular disease on the risk of major outcomes in patients with type 2 diabetes - Mohammedi, K; Woodward, M; Marre, M; Colagiuri, S; Cooper, M; Harrap, S; Mancia, G; Poulter, N; Williams, B; Zoungas, S; Chalmers, J (BioMed Central, 2017)
Background: Microvascular disease is associated with a high risk of macrovascular events in patients with type 2 diabetes, but the impact of macrovascular disease on the risk of microvascular events remains unknown. We sought to evaluate the respective effects of prior microvascular and macrovascular disease on the risk of major outcomes, including microvascular events, in these patients. Methods: Participants in the Action in Diabetes and Vascular Disease: PreterAx and DiamicroN Modified-Release Controlled Evaluation (ADVANCE) trial (n=11140) and the ADVANCE-ON post-trial study (n=8494) were categorized into 4 groups at baseline: dual absence of microvascular or macrovascular disease (n=6789), presence of microvascular disease alone (n=761), macrovascular disease alone (n=3196), and both (n=394). Outcomes were all-cause mortality, major macrovascular events (MACE), and major clinical microvascular events. Results: All-cause mortality, MACE, and major clinical microvascular events occurred in 2265 (20%), 2166 (19%), and 807 (7%) participants respectively, during a median follow-up of 9.9 (inter-quartile interval: 5.6–10.9) years. The adjusted hazard ratios [95%CI] of death, MACE, and major clinical microvascular events were each greater in patients with baseline microvascular disease (1.43 [1.20-1.71], 1.64 [1.37-1.97], and 4.74 [3.86-5.82], respectively), macrovascular disease (1.43 [1.30-1.57], 2.04 [1.86-2.25], and 1.26 [1.06-1.51]) or both (2.01 [1.65-2.45], 2.92 [2.40-3.55], and 6.30 [4.93-8.06]) compared with those without these conditions. No interaction was observed between baseline microvascular and macrovascular disease for these events. The addition of microvascular disease (change in c-statistic [95%CI]: 0.005 [0.002-0.008], p=0.02) or macrovascular disease (0.005 [0.002-0.007], p<0.0001) considered separately or together (0.011 [0.007-0.014], p<0.0001) improved the discrimination and the classification (integrated discrimination improvement (IDI): 0.013 [0.010-0.016], p<0.001; net reclassification improvement (NRI): 0.021 [0.011-0.032], p<0.001) of the risk of all-cause mortality. Microvascular disease improved discrimination (0.009 [0.003-0.014]) and classification (IDI: 0.008 [0.006-0.010]; NRI: 0.011 [0.001-0.020]) of MACE. Baseline macrovascular disease modestly enhanced IDI (0.002 [0.001-0.002]) and NRI (0.041 [0.002-0.087]), but not discrimination, of major clinical microvascular events. Conclusions: Microvascular and macrovascular disease are independently associated with the 10-year risk of death, MACE, and major clinical microvascular events in patients with type 2 diabetes. The coexistence of these conditions was associated with the highest risks.